Learning Innovations in Physical Education, Sports, and Health During the Covid-19 Pandemic - Prasetyo, Adhi; Irvan Sir; Amir, Atmam (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The COVID-19 pandemic has altered our lives forever. The realm of education is one of them. The learning process is disrupted, yet as a result of this, new educational innovations have evolved, which indirectly drive education down a more advanced path by incorporating technology. As a result, during the COVID-19 pandemic, this study takes a qualitative method with good learning analytic tools and learning innovations. Furthermore, data for this study was gathered through tracking numerous learning sources, with an emphasis on online learning that makes use of technology, particularly the internet network. Students have the most trouble with online learning in physical education, sports, and health since they emphasize movement activities, but online learning has more students just sitting in front of the electronic devices used. Furthermore, learning on the network is frequently hampered by a sluggish internet connection, which might obstruct the learning process. When learning takes place in person, various hurdles arise. The most significant of these is the time limit for face-to-face sessions at school, which forces educators to condense the material to be delivered. In practice, students must create video recordings in order to obtain the psychomotor value of students in the worksheet because the primary goal of this subject for elementary school students is to promote children's movement activities.